NOVEL PHARMACEUTICAL COCRYSTAL OF TELMISARTAN AND HYDROCHLOROTHIAZIDE: CO-CRYSTALS - KULKARNI, ALPANA; SHETE, SWAPNIL; HOL, VISHAL; BACHHAV, RITESH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Telmisartan (TEL), commonly used antihypertensive, is poorly soluble in water and has limited and variable bioavailability. Commercially, TEL is available as a single drug and in combination with hydrochlorothiazide (HYZ). Researchers have developed cocrystals of TEL with coformers, namely, oxalic acid, glutaric acid, and saccharin. An attempt was made to prepare the cocrystals of TEL with HYZ, an active pharmaceutical ingredient (API) itself so that both the APIs are available in a single tablet. The present study was aimed at enhancement in solubility of TEL by formation of its cocrystals. Methods: The cocrystals of TEL with HYZ, in different stoichiometric ratios (1:0.5, 1:1, and 1:2), were prepared by solvent coevaporation and liquid-assisted grinding methods. The cocrystals, consisting of TEL:HYZ (in 1:0.5 ratio and 1:1 ratio), depicted maximum yield, drug content, saturation solubility, and flow properties. These cocrystals were characterized by X-ray analysis, infrared spectroscopy, and thermal analysis. Results: The crystal structure of TEL-HYX revealed that it was a cocrystal, since no proton was transferred between the TEL and HYZ molecules. It was predicted that two molecules are associated through a hydrogen bond between an acidic group of TEL and sulfonamido group of HYZ. The cocrystallization improved the solubility of TEL 7 times. In vitro release rate of tablets of cocrystals was higher than that of marketed TEL tablets. HYZ has a potential to form the cocrystals of TEL. Conclusion: The objective of improvement in the solubility of TEL was successfully achieved by the formation of cocrystals of TEL: HYZ.